Meeting Report: 38th Annual Scientific Meeting and Workshops of the Society of Cardiovascular Anesthesiologists. (April 2017) - Shaw, Andrew D.; Fox, Amanda A.; Eaton, Michael P.
Abstract : Published ahead of print December 15, 2016.